Preservation of Javanese Language on Ganjar Pranowo's Conversation in Pandemic of COVID-19 - Farichah, Umi; Rakhmawati, Ani; Wardani, Nugraheni Eko (Humaniora: Journal of Indonesia Culture and Society, 2021)
The research aimed to see a relevance of the preservation of the Javanese language in Javanese conversations that Ganjar Pranowo carried out during the COVID-19 pandemic. The resulting data was about the level in the language that included word level, phrase level, and sentence level. Also, several manners, unggah ungguh, and ethics were produced that could become examples or role models for the people of Central Java. The research applied a qualitative method. The data source was the utterances contained in the uploads of Ganjar Pranowo in the form of video recordings that included primary data in the form of utterances or parts of spoken speech from various speeches and communications from the people of Central Java with Ganjar Pranowo. The results show that preservation of the Javanese language through conversations between leaders and the community has positive implications. This means that the preservation of the Javanese language is carried out optimally in the social sphere. This activity is well recorded and uploaded on social media, Ganjar Pranowo, a figure who has high credibility. The social sphere is an important component used to preserve Javanese language, culture, and traditions.